Comparative study of 20 GY in 5 fraction versus 30 GY in 10 fraction palliative radiation in advanced inoperable head and neck cancer. - Lohani,Sauharda (2020)
EXECUTIVE SUMMARY Background: There is a wide variation in treatment of advanced inoperable head and neck cancer in terms of palliative radiotherapy schedule. There are treatment challenges in terms of symptoms palliation, considering complex anatomical structure and poor survival. Various palliative radiotherapy schedules are on practice worldwide, considering their setup and resources available. This study is designed to compare the efficacy of 20 Gy/5# palliative RT to 30 Gy/10# palliative RT, in terms of palliation of pain and dysphagia. Methodology: An observational comparative analytical study was conducted in National Academy of Medical Science (NAMS), Bir Hospital after ethical approval from Institutional Review Board (IRB) of NAMS. Patient with an advanced head and neck cancer who visited in an outpatient basis were selected based on its inoperability, metastatic status, performance status, and prognosis of disease, and cases were discussed intra and interdepartment. The pain and dysphagia score of these patients were assessed and recorded. Patients were then randomly assigned into two groups one with 20 Gy in 5 fraction over 1 week and other with 30 Gy in 10 fractions over 2 weeks. 44 patients were enrolled in the study. Assessment of pain was done as per 10-point NRS (Numerical Rating Score and dysphagia was graded as per common toxicity criteria CTC v.2.0 Dysphagia grading Scale. Follow-up evaluation was done 1-week post treatment, and the changes in pain score and dysphagia grade was recorded. Results: Of the 44 patients enrolled in 20 Gy/5# and 30 Gy/10#, all participants in the study received the planned treatment of radiotherapy. Age, Performance status,, gender and primary site of malignancy were comparable between the two groups. The mean pain score before treatment in 30 Gy/10# arm is 7.22(±1.06) and in 20 Gy/5# arm is 6.81± (1.05), [p value- 0.20]. The mean pain score after treatment in 30 Gy/10# arm is 4.13 (± 1.20) and 20 Gy/5# arm is 4.27(±1.51), [p value- 0.74]. This reduction of pain symptom within the group is of statistically significant. The mean difference in pain between two groups is 0.55 (p value - 0.154). There was also significantly reduction in strong opoid analgesic requirement post radiation. There was also improvement in dysphagia post treatment between the two arms. 7 out of 44 patients had Grade III dysphagia, of which 4 were in 30Gy/10# arm and 3 were in 20Gy/10# arm, however post palliative RT, none of the patient were in Grade III dysphagia.